2016
DOI: 10.1016/j.bjm.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth-promoting bacteria on the growth and fructan production of Agave americana L.

Abstract: The effect of plant growth-promoting bacteria inoculation on plant growth and the sugar content in Agave americana was assessed. The bacterial strains ACO-34A, ACO-40, and ACO-140, isolated from the A. americana rhizosphere, were selected for this study to evaluate their phenotypic and genotypic characteristics. The three bacterial strains were evaluated via plant inoculation assays, and Azospirillum brasilense Cd served as a control strain. Phylogenetic analysis based on the 16S rRNA gene showed that strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…Similar to the results of this study, De La Torre-Ruiz et al 8 indicated that inoculation with PGPB exerted a positive effect on the growth of Agave americana plants under glasshouse conditions. The strains of Acinetobacter calcoaceticus, Pseudomonas mosselii, and Rhizobium daejeonense all had positive effects on plant DW, PSD, PL, and root length compared with uninoculated control plants of Agave Americana.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to the results of this study, De La Torre-Ruiz et al 8 indicated that inoculation with PGPB exerted a positive effect on the growth of Agave americana plants under glasshouse conditions. The strains of Acinetobacter calcoaceticus, Pseudomonas mosselii, and Rhizobium daejeonense all had positive effects on plant DW, PSD, PL, and root length compared with uninoculated control plants of Agave Americana.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the results of this study, De La Torre‐Ruiz et al . indicated that inoculation with PGPB exerted a positive effect on the growth of Agave americana plants under glasshouse conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). P. mosselii was originally isolated from clinical specimens and some isolates have biotechnological importance, including for agriculture (Dabboussi et al 2002;De La Torre-Ruiz et al 2016). P. guariconensis was identified colonizing the rhizosphere of leguminous Vigna unguiculata and has potential to solubilize inorganic phosphates and to promote plant growth (Toro et al 2013;Patel et al 2015).…”
Section: Resultsmentioning
confidence: 99%